SUN-480 Melanocortin-4 Receptor In Spotted Sea Bass: Cloning, Tissue Distribution, Physiology And Pharmacology - Hou, Zhi-Shuai (J Endocr Soc, 2019)
Melanocortin-4 receptor (MC4R) plays important roles in the regulation of multiple physiological processes including energy homeostasis, reproduction, sexual function and other functions in mammals. Although studies of teleost melanocortin system are less extensive, some studies revealed that teleost MC4Rs have different physiological functions and pharmacological characteristics when compared to mammalian MC4Rs. For example, mammalian MC4Rs are primarily expressed in the central nervous system whereas teleost MC4Rs are also expressed in peripheral tissues. Moreover, teleost MC4Rs have much higher basal activities compared to mammalian MC4Rs. In this study, we investigated Spotted sea bass (Lateolabrax maculatus) LmMC4R physiology and pharmacology. We identified Spotted sea bass mc4r (Lmmc4r), consisting of a 984 bp open reading frame encoding a protein of 327 amino acids. Sequence of MC4R was homologous to those of several teleost MC4Rs (over 80%) and human MC4R (hMC4R, over 70%). qRT-PCR and in situ hybridization revealed that Lmmc4r transcripts were highly expressed in brain, followed by pituitary and liver. We also revealed that brain Lmmc4r transcripts were down-regulated in the long-term and short-term fasting challenges. LmMC4R was further demonstrated to be a functional receptor by pharmacological studies. Compared to hMC4R, LmMC4R exhibited lower maximal ligand binding and higher basal activity. Endogenous ligands α-melanocyte stimulating hormone (α-MSH) and adrenocorticotropin (ACTH) could bind to LmMC4R and induce intracellular cAMP production dose-dependently. Three small molecules THIQ, Ipsen 5i and ML00253764 were not able to displace (125)I-NDP-MSH but could stimulate intracellular cAMP accumulation, suggesting that they bound to LmMC4R allosterically. We isolated the brain cells of Spotted sea bass and in vitro studies indicated that gene expressions of neuropeptide Y (npy), Agouti-related peptide (agrp) and growth hormone (gh) were down-regulated when the brain cells were treated with α-MSH. In summary, we cloned Spotted sea bass MC4R, and showed that it had different pharmacological properties compared to hMC4R, and potentially different functions.